Review of Compounds and Pharmacological Effects of Delphinium - Sitan Chen; Lijun Meng; Fatma M. El-Demerdash; Li Zhou; Syed Arif Hussian Rizvi; Lili Cui; Wenyi Kang (Journal of Chemistry)
Plants of Delphinium are herbal medicine used in the Tibet region with whole grass as a drug, which have the effects of analgesic, antibacterial, antipyretic, and anticancer. The main bioactive compounds are alkaloids, flavonoids, and sterols. This review summarized the compounds and pharmacological effects of Delphinium and provides a reference for further research on Delphinium.